E-Office Software to Promote Paperless Working Environment (Journal of Asian Development Studies, 2025)
This paper emphasizes digital transformation and a paperless Punjab Assembly in today’s modern era. It highlights e-parliaments in light of the Digital Maturity Index of IPU. The focus is on how we can control environmental pollution and how a paperless assembly can help reduce paper wastage, thereby contributing to a cleaner and greener environment. It also discusses how this initiative can support the Government of Punjab and the CPA in achieving the SDG goals, enhance the performance of the Secretariat, and assist members in the legislative process. Realizing Pakistan's status of being one of the top 10 countries vulnerable to climate change, the new Article 9A has been inserted in the Constitution of the Islamic Republic of Pakistan 1973 through 26th Amendment: “9A. Clear and Healthy Environment - Everyone has the right to a clean, healthy and sustainable environment.”